Intelligent and Modular Based Attendance System - Haseeb Tanveer; Fazal ur Rehman (Universitas Pendidikan Indonesia, 2023)
This research paper presents a novel approach for solving Schools/Colleges/Universities/Offices attendance related issues using modular based approach. Radio Frequency Identification System (RFID) is used for person identification. An android application is built which communicates with RFID readers. A completely separate database is developed which is continuously automatically updated from android application. Android applications are developed based on modular approach so that customized system can be provided according to the institution requirements. System features were tap and go based attendance system, automated attendance reports to superiors, integrated door lock with attendance system, turnstile control, real time picture using front camera of smart mobile, institution entry/exit-based attendance solution, individual attendance system for each department/classrooms/supervisors and message/email to parents/superiors, parent-teacher communications. Results suggest that the institution felt more comfortable with modular based approach. Parents were satisfied due to timely attendance messages of their children.